IMPROVING COGNITIVE AND PEDAGOGICAL OF UNDERGRADUATE SCIENCE EDUCATION STUDENTS IN INTEGRATED SCIENCE COURSE THROUGH SIMULATION METHOD - Setiawan, B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
The purpose of this research is then subdivided in to two spesific goal as follows to describe the cognitive competence of students or junior high science teacher candidates reflected in the activities of pretest and posttest on Integrated Science course. Research design using pre-experimental research design to study design one group pretest-posttest design. The conclusions obtained in this study were 1) Observation of simulation activities or pedagogical students each, student obtained score of 1.9 to 2.5 was categorized good.